Otitis media in children: Which phenotypes are most linked to allergy? A systematic review. Issue 3 (11th January 2021) - De Corso, Eugenio; Cantone, Elena; Galli, Jacopo; Seccia, Veronica; Lucidi, Daniela; Di Cesare, Tiziana; Ottaviano, Giancarlo; Sergi, Bruno; Paludetti, Gaetano; Fetoni, Anna Rita
Abstract: Background: Allergic rhinitis is a common childhood disease responsible for a major impact on quality of life and healthcare resources. Many hypotheses have been proposed to explain the link between allergy and otitis media, although a definitive mechanism has not been identified yet. One of the major critical points is that authors failed in distinguishing among different phenotypes of middle ear inflammation. This review pointed out literature evidence from the laboratory and clinical experience linking allergy to different phenotypes of otitis media in children. Methods: We performed a systematic review in accordance with the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) process. Our search yielded 3010 articles that were finally screened. This resulted in 20 manuscripts of which the full texts were included in a qualitative analysis. We paid particular attention in distinguishing among phenotypes of otitis media. Results: Clinical evidence and analyses of biomarkers suggested that allergy may be linked to some phenotypes of otitis media and, in particular, to otitis media with effusion (OME) and acute re‐exacerbations in children with middle ear effusion. It was not possible to perform the analysis for allergy and acute and chronic otitis media because of paucity and heterogeneity of data. Conclusion: Allergy should be considered in the diagnostic workup of children with OME as well as OME should be excluded in children with persistent moderate to severe AR. In these cases, clinicians should evaluate prompt and accurate treatment of allergy in improving outcomes, although futures studies are required to increase evidence supporting that anti‐allergy treatment may be effective in the recovery and outcome of otitis media with effusion.